Comparative Study of Quality Assurance Standards between the Indonesian National Accreditation Board and Malaysian Qualifications Agency in Higher Education - Komara, Endang; Nuraeni, Iin Indra; Tio, Lina; Marlina, Reni (Perkumpulan Psikologi Transformasi Indonesia (P2TI), 2025)
This research aimed to identify differences and similarities in quality assurance standards and guidelines between the Indonesian National Accreditation Board (BAN-PT) and the Malaysian Qualifications Agency (MQA). It focused on how each country implements these standards in curriculum, facilities, human resources, research, community service, and cooperation. It highlights challenges such as interpreting standards and adapting to evolving accreditation criteria. The analysis was taken based on official documents, regulations, and standards from both BAN-PT and MQA, assessing the impact on state and private higher education. The objectives included determining quality assurance standards and guidelines, identifying regulatory differences and similarities, and evaluating the implementation of these standards. Quality assurance standards in Indonesian and Malaysian higher education use a qualitative comparative approach; the research involved literature studies, relevant population and sample selection, and detailed data collection and analysis techniques. The study's findings indicated that Indonesia relies on the Regulation of the Minister of Education and Culture No. 3 of 2020 and ISO standards, with BAN PT overseeing accreditation. MQA uses the Malaysian Qualifications Framework to enhance education quality and international recognition in Malaysia. The research identified challenges such as aligning national and international standards in Indonesia and the significant impact of MQA's student-centered approach in Malaysia. Despite differences, both agencies ensure quality and competitiveness in higher education, contributing to continuous improvement and adherence to international standards